A new combination in Parkinsonia (Caesalpinoideae/Fabaceae): Parkinsonia andicola - Romão, Marcos Vinicius Varjão; Mansano, Vidal Freitas (Phytotaxa, 2018)
A phylogenetic study with molecular data for the Peltophorum group (Haston 2005: 1359) indicated that Parkinsonia Linnaeus (1753: 375) and Cercidium Tulasne (1844: 133), recognized as distinct genera (Johnston 1924: 61, Carter 1974: 17), are paraphyletic, and when lumped, together form a well-sustained monophyletic group.